2015
DOI: 10.1007/s11432-014-5264-8
|View full text |Cite
|
Sign up to set email alerts
|

Wideband underwater sonar imaging via compressed sensing with scaling effect compensation

Abstract: By exploiting the sparsity of the imaging scene, compressed sensing (CS) imaging may provide an effective solution to cope with the tradeoff of high azimuth resolution and wide swath in synthetic aperture sonar imaging. However, existing CS imaging methods are based on narrowband signal model and the scaling effect on the echoes is normally omitted, which may seriously affect the ultimate image reconstruction performance. This paper establishes the wideband CS underwater sonar imaging model at first, where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Meanwhile, the cross-track interferometry synthetic aperture radar (XTI-SAR) is usually used for the digital elevation model (DEM) generation [16,17,18] in the side-looking application because the interferometry phases among cross-track multiple receivers are sensitive to the target’s height. Nevertheless, few studies can be found on GMTI for XTI-SAR, though many real systems with cross-baselines still only have strong demands on the GMTI [19,20,21,22,23,24,25,26,27,28]. For example, the airborne navigation or fire-control radars are normally mounted on the plane nose with a forward-looking array antenna, where the receivers are all distributed in the plane perpendicular to the flying track.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the cross-track interferometry synthetic aperture radar (XTI-SAR) is usually used for the digital elevation model (DEM) generation [16,17,18] in the side-looking application because the interferometry phases among cross-track multiple receivers are sensitive to the target’s height. Nevertheless, few studies can be found on GMTI for XTI-SAR, though many real systems with cross-baselines still only have strong demands on the GMTI [19,20,21,22,23,24,25,26,27,28]. For example, the airborne navigation or fire-control radars are normally mounted on the plane nose with a forward-looking array antenna, where the receivers are all distributed in the plane perpendicular to the flying track.…”
Section: Introductionmentioning
confidence: 99%
“…To solve the above problem, methods based on dictionary learning [16] or joint sparse recovery algorithms [14,17] are proposed, but they are still established on the foundation of discrete dictionary or consider the high order Taylor approximation of the off-grid error. Besides, a modified L1-norm minimization algorithm is proposed to solve the model mismatch problem in wideband underwater sonar imaging [18], however, it is not suitable for the narrowband signal model in SAR imaging. By contrast, the model of atomic norm [19,20], which deals with sparse recovery problem directly on the continuous bearing space instead of discrete grids, has been studied in line spectral estimation and direction of arrival (DOA) estimation to solve the off-grid problem [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Multifunctional SAR with large-area static scene imaging and ground moving target indication (SAR/GMTI) has drawn much more attentions in recent past decades [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32]. In the most of applications, not only the point moving targets but also the distributed moving targets are interested.…”
Section: Introductionmentioning
confidence: 99%